2010
DOI: 10.1038/ijo.2010.2
|View full text |Cite
|
Sign up to set email alerts
|

Relation between body mass index, physical inactivity and use of prescription drugs: the Doetinchem Cohort Study

Abstract: Background: Obesity and physical inactivity are associated with several diseases such as diabetes, cardiovascular diseases, musculoskeletal complaints, osteoporosis, certain types of cancer and depression. However, few data are available on the specific types of medication associated with obesity and physical inactivity. Objective: The aim of this study was to determine the independent association of body mass index (BMI) and physical inactivity with use of specific classes of prescription drugs, and the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The lower BMI of high-level activity participants compares with previous research that reported a lower BMI was associated with more steps per day (Chan et al, 2003; Strath et al, 2011; Tudor-Locke et al, 2001). In this study, low-level physical activity participants reported a greater use of medications; these results are similar to research in which physical inactivity in women was associated with an increased use of several prescription medications, such as cardiovascular drugs and alimentary tract and metabolism drugs (Milder, Klungel, Mantel-Teeuwisse, Verschuren, & Bemelmans, 2010). …”
Section: Discussionsupporting
confidence: 86%
“…The lower BMI of high-level activity participants compares with previous research that reported a lower BMI was associated with more steps per day (Chan et al, 2003; Strath et al, 2011; Tudor-Locke et al, 2001). In this study, low-level physical activity participants reported a greater use of medications; these results are similar to research in which physical inactivity in women was associated with an increased use of several prescription medications, such as cardiovascular drugs and alimentary tract and metabolism drugs (Milder, Klungel, Mantel-Teeuwisse, Verschuren, & Bemelmans, 2010). …”
Section: Discussionsupporting
confidence: 86%
“…The prescription medication data in NHANES are based on home interviews where medication containers physically located in the home are reviewed to obtain accurate information and reflect actual patient use more closely than data on what medications were prescribed, sold, or dispensed in the previous year. Previous research has relied on selfreports (7), prescription sales and doctor’s office data (31), or retrospectively linked drug dispensing records (32). Studies on long-duration sleepers are limited due to small sample sizes or combining long- duration and average-duration sleepers (2).…”
Section: Discussionmentioning
confidence: 99%
“…Similar changes were reported by Dilla et al following for a 12-month period 738 patients with a mean age of 66 years and BMI of 30.6 kg/m 2 : each unit gain in BMI was associated with a 20.0% increase in costs for BMI gainers while loss of one unit decreased these costs by 8.0% in non-BMI gainers [ 13 ]. Milder et al also reported that obese persons used more prescription drugs of several types, particularly cardiovascular drugs (OR 3.83 in men and 2.80 in women) and diabetes drugs (OR 5.72 in men and 3.92 in women) than normal weight persons [ 14 ]. Future healthcare costs were also higher for overweight persons, especially for those with BMIs ≥ 30 kg/m 2 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%